MiR‐145‐5p inhibits proliferation and inflammatory responses of RMC through regulating AKT/GSK pathway by targeting CXCL16. Issue 4 (23rd November 2017) - Wu, Junbiao; He, Yu; Luo, Yining; Zhang, Lei; Lin, Hua; Liu, Xusheng; Liu, Bihao; Liang, Chunling; Zhou, Yuan; Zhou, Jiuyao
Abstract : The main pathological characteristics of chronic glomerulonephritis (CGN) are diffuse mesangial cells proliferation and inflammatory responses. Our previous studies have confirmed that miR‐145‐5p was abnormally elevated in CGN rats, but its mechanism remains unclear. Therefore, this study aimed to elucidate the mechanism of miR‐145‐5p in regulation of renal mesangial cells proliferation and inflammatory responses. In vivo study, the cationic bovine serum albumin (C‐BSA)‐induced CGN rat model was established, and the content of miR‐145‐5p in renal was examined by qRT‐PCR, meanwhile, we also determined the renal function and inflammatory infiltrate. In vitro, the cell proliferation rate, cell cycle and inflammatory changes of rat mesangial cells (RMCs) were measured. Our results suggested that miR‐145‐5p extended the G0‐G1 phase, shortened S phase, inhibited cell proliferation and suppressed inflammatory responses in RMCs. Moreover, miR‐145‐5p inhibited CXCL16 protein expression through binding the 3′‐UTR of CXCL16, suppressed AKT/GSK signaling pathway, and decreased expression of inflammation related mRNAs, such as IL‐1α, IL‐2, IL‐6, and TNF‐α mRNAs. Further, locking CXCL16 alleviated inflammatory reactions and down‐regulated AKT/GSK pathway in RMCs. Above all, we concluded that miR‐145‐5p inhibited proliferation and inflammatory responses of RMCs through regulation of AKT/GSK pathway by targeting CXCL16. Abstract : Our study aimed to elucidate the mechanism of miR‐145‐5p in regulation of renal mesangial cell proliferation and inflammatory responses. Base on the in vivo and in vitro study, the results suggested that miR‐145‐5p inhibited proliferation and inflammatory responses of RMCs through regulation of AKT/GSK pathway by targeting CXCL16.